Cardiac rehabilitation outcomes following a 6-week program of PCI and CABG Patients - Jelinek, Herbert F.; Huang, Zhaoqi; Khandoker, Ahsan H.; Chang, Dennis; Kiat, Hosen (Frontiers in Physiology, 2013)
Coronary artery events requiring intervention are associated with depressed cardiac autonomic function. Whether a 6-week cardiac rehabilitation (CR) differs in effectiveness in improving exercise capacity (6MWT), cardiorespiratory function (peakVO2), and autonomic function (HRV) following either cardiac bypass surgery (CABG) or percutaneous coronary revascularization (PCI) is unknown. The current study therefore compared the change in 6MWT and peak VO2 to HRV variables following a 6-week CR program and with patients having either PCI or CABG. Thirty-eight patients, (PCI, n = 22 and CABG, n = 16) participated in the CR program and results for pre and post 6 min walk test (6MWT), peakVO2, and heart rate variability (HRV) were obtained. Our study has shown that a 6 weeks program following either PCI or CABG improves function. However, the effect on post-CABG differs to that of post-PCI patients. The change in distance walked (6MWT, metres) was higher in the CABG (Δ6MWT: 61, p < 0.001) compared to the PCI group (Δ6MWT: 41, p < 0.001). Maximum exercise capacity (peak VO2, ml/kg.min) also changed significantly with a greater change in the CABG group (ΔPCI: 0.7, p < 0.001; ΔCABG: 1.0, p < 0.001) but did not reach normal population values. Although an improvement in HRV parameters was noted for the PCI group, a statistically significant improvement in HRV was observed only in the CABG group for the following; SDNN (ms) (baseline vs. post-rehabilitation (median ± IQR): 31.2 ± 25.6 vs. 51.8 ± 23.1, p < 0.01), RMSSD (19.32 ± 19.9 vs. 42.1 ± 34.2, p < 0.01); LF (ms2) (191 ± 216 vs. 631 ± 693, p < 0.01) and HF (107 ± 201 vs. 449 ± 795.0, p < 0.05). A significant interaction in the PCI group but not in the CABG group was observed using correlation analysis between the 6MWT and peak VO2 with HRV parameters indicating that being healthier that is, a better 6MWT and peak VO2 led to better HRV results but no significant effect of CR in the PCI group. When the results were investigated for baseline 6MWT and peak VO2 effect using a covariate analysis, a significant influence of CR on HRV parameters was retained in the CABG group (p = 0.0072). Our study indicates that a 6-weeks CR program benefits both patient groups in terms of exercise capacity, cardiorespiratory function and autonomic nervous system modulation of heart rate, with CABG patients showing the most improvement. HRV can be a useful additional variable to gauge cardiac function following CR.